Indian bead-weaving patterns : chain-weaving designs, bead loom weaving, and bead embroidery : an illustrated "how-to" guide - Goodhue, Horace (Bead-Craft, 1989)
A basic guide to Indian bead weaving containing over 200 instructional illustrations and photographs of forty-seven bead-work projects.